PELATIHAN PRAKTIKUM IPA BERBASIS LINGKUNGAN BAGI GURU SMP KABUPATEN ACEH TIMUR - Nurhafidhah; Mauliza; Hasby (Global Science Society, 2022)
Practical activities have a very important role in science learning, because they can improve the quality of learning which leads to improving the quality of students. The purpose of implementing this community service activity is to provide knowledge and skills to science subject teachers in conducting experiments through science practicum by utilizing environmental-based materials and tools. In addition, it is also expected to support the Continuous Professional Development Program through the Zoning-Based Learning Competency Improvement (PKP) organized by the Ministry of Education and Culture through the Directorate General of Teachers and Education Personnel (Ditjen GTK). This activity was carried out at SMP Negeri 1 Idi, with the number of participants as many as 70 science teachers at the junior high school level in Kabupaten East Aceh. The methods used in this activity are socialization, training and assistance in the use of environmental-based science practicum tools and materials, as well as education on the use of environment-based science practicum guides. The results of the positive participant response activities were seen from the increase in the interaction of participants' questions and answers during the discussion and the results of the teacher's professional assessment questionnaire answers on average, namely 81.6% belonging to the good category